The Value-Oriented And Competency-Based Approaches In Modern Education: Challenges (Journal of Pedagogical Inventions and Practices, 2025)
This article examines the competency-based and value-oriented approaches to education quality in the context of a consumer society. It explores the limitations of competency-based education, which primarily caters to immediate labor market demands, and highlights the necessity of a value-based framework that fosters creativity, personal growth, and social responsibility. The paper also discusses the role of innovative learning (IL) methodologies in transforming traditional education, emphasizing the need for flexible, individualized learning trajectories. By integrating theoretical insights with practical applications, the study underscores the significance of innovation in ensuring education quality, preparing students for dynamic socio-economic environments, and fostering a culture of continuous learning